Thermally Driven Structure and Performance Evolution of Atomically Dispersed FeN4 Sites for Oxygen Reduction. (11th November 2019) - Li, Jiazhan; Zhang, Hanguang; Samarakoon, Widitha; Shan, Weitao; Cullen, David A.; Karakalos, Stavros; Chen, Mengjie; Gu, Daming; More, Karren L.; Wang, Guofeng; Feng, Zhenxing; Wang, Zhenbo; et al.
Abstract: FeN4 moieties embedded in partially graphitized carbon are the most efficient platinum group metal free active sites for the oxygen reduction reaction in acidic proton‐exchange membrane fuel cells. However, their formation mechanisms have remained elusive for decades because the Fe−N bond formation process always convolutes with uncontrolled carbonization and nitrogen doping during high‐temperature treatment. Here, we elucidate the FeN4 site formation mechanisms through hosting Fe ions into a nitrogen‐doped carbon followed by a controlled thermal activation. Among the studied hosts, the ZIF‐8‐derived nitrogen‐doped carbon is an ideal model with well‐defined nitrogen doping and porosity. This approach is able to deconvolute Fe−N bond formation from complex carbonization and nitrogen doping, which correlates Fe−N bond properties with the activity and stability of FeN4 sites as a function of the thermal activation temperature. Abstract : Aktiv durch Eisen : In partiell graphitisierten Kohlenstoff eingebettete FeN4 ‐Gruppen sind effiziente aktive Zentren für die Sauerstoffreduktion in sauren Protonenaustauschmembran‐Brennstoffzellen. Die Mechanismen, die zur Bildung dieser aktiven Zentren führen, wurden durch Einführung von Fe‐Ionen in Stickstoff‐dotierten Kohlenstoff, gefolgt von kontrollierter thermischer Aktivierung untersucht.